A Critique on the Book The Oxford Handbook of Iranian History - Behzad Karimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The subject of this article is the evaluation and critique of The Oxford Handbook of Iranian History edited by Touraj Daryaee. The critic believes that this work, despite having valuable information, has formal and content problems, including the references and bibliography of the articles which are not uniform, the articles are not balanced, the content of the articles does not follow a single pattern, it has not dealt with some important historical periods, some articles are non-historical and very specialized, the idea of Iran as a central idea has been neglected and finally, the book needs to be reviewed in terms of the translation. The type of collection of articles with a common theme has a single agenda in terms of form and content, but this collection lacks such a feature in various ways. The book is also caught in the crossroads of academic writing and attracting non-specialist audiences. The greatest drawbacks of this work as mentioned above can be considered the negligence of the study of some expected and important historical periods, which has undeniably damaged the credibility of the book.